2001
DOI: 10.1007/pl00011338
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Peripheral Revascularisation with Excimer Laser: Equipment, Technique and Results

Abstract: Laser angioplasty has been evaluated for coronary applications since the early 1980s. Early complications of dissection, perforation and thermal injury led to a loss of enthusiasm for this technique. Recent advances in catheter development, including optimally spaced laser fibres, athermic 308 nm wave-length catheters, and saline infusion techniques have produced larger laser channels, minimised thermal injury and significantly reduced vessel dissection. This improvement in equipment and technique has led to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…[42][43][44][45][46] The experience with laser intervention in the late 1980s was somewhat disappointing in terms of durability, but this was related to the type of lasers utilized and associated thermal injury. [42][43][44] Recent advances in catheter design and technique, including saline infusion, have minimized the thermal energy associated with laser therapy and reduced the risk of vessel dissection. The results of the Laser Atherectomy for Critical Ischemia (LACI-1) pilot study are promising for patients with nonhealing wounds.…”
Section: Atherectomy and Plaque Ablationmentioning
confidence: 99%
See 1 more Smart Citation
“…[42][43][44][45][46] The experience with laser intervention in the late 1980s was somewhat disappointing in terms of durability, but this was related to the type of lasers utilized and associated thermal injury. [42][43][44] Recent advances in catheter design and technique, including saline infusion, have minimized the thermal energy associated with laser therapy and reduced the risk of vessel dissection. The results of the Laser Atherectomy for Critical Ischemia (LACI-1) pilot study are promising for patients with nonhealing wounds.…”
Section: Atherectomy and Plaque Ablationmentioning
confidence: 99%
“…Debulking the SFA or popliteal artery utilizing laser technology has also helped to improve outcomes and durability for femoro-popliteal disease. [42][43][44][45][46] The experience with laser intervention in the late 1980s was somewhat disappointing in terms of durability, but this was related to the type of lasers utilized and associated thermal injury. [42][43][44] Recent advances in catheter design and technique, including saline infusion, have minimized the thermal energy associated with laser therapy and reduced the risk of vessel dissection.…”
Section: Atherectomy and Plaque Ablationmentioning
confidence: 99%
“…[72][73][74][75] Recent advances in catheter design and technique, including saline infusion, have minimized the thermal energy associated with laser therapy and reduced the risk of vessel dissection. The results of the Laser Atherectomy for Critical Ischemia (LACI-2) pilot study are promising for patients with non-healing wounds.…”
Section: Excimer Laser Atherectomy (Photoablation)mentioning
confidence: 99%
“…Treating percutaneously CLI can improve symptoms, save limbs, or, at least, provide acceptable vascular bed for open surgical revascularization. With that in mind, the outcomes of excimer laser angioplasty in CLI as reported by Boccalandro et al [1] and others as well [3, 4] are realistic and encouraging. Specifically, Boccalandro et al [1] reported an 84% procedural success, 88% limb salvage when laser recanalization was combined with surgical revascularization, and 72% actual freedom from surgical revascularization or limb loss was achieved.…”
mentioning
confidence: 76%